The Optative Movement of Dr Jekyll and Mr Hyde's Addicts. Issue 2 (2015) - Colman, Adam
Abstract : This essay considers how formal techniques in Robert Louis Stevenson's Strange Case of Dr Jekyll and Mr Hyde reflect the Victorian era's medical discourse. Particularly, I consider the rise of nineteenth-century addiction discourse (widely acknowledged as influential for Stevenson) and the corresponding modal dynamics of addiction that Stevenson discovered. Stevenson uses the optative grammatical mood in Dr Jekyll and Mr Hyde while depicting habitual drinkers of alcohol, emphasizing wishes rather than actualized satisfaction, and I argue that those characters in turn produce, more broadly, a story full of optative, desirous movement into realms of possibility. Drawing from possible worlds theorists' suggestive interest in the Jekyll and Hyde story, I then examine Stevenson's own emphasis on addictive pursuit of possibility rather than attainment. His repetitive drinkers such as Jekyll and the lawyer Utterson follow their incessant wishes and imaginatively move toward mystery through avatars (in Jekyll's case) or explore through letters, dreams, and gossip (in Utterson's). They move vicariously, mediated from actuality and attainment, in scenes characterized by optative language. Such formal implications of addiction discourse have yet to be explored, and Dr Jekyll and Mr Hyde presents an especially rich starting point for that exploration.